Stability indicating RP‐HPLC method for methylcobalamin determination in different dosage forms: Application to photodegradation kinetics and pH rate profiling. Issue 15 (14th June 2022) - Amer, Mona M.; Kamal, Amira H.; Hammad, Sherin F.; Habib, Ahmed A.
Abstract : A stability‐indicating RP‐HPLC method for methylcobalamin determination was developed. Stress degradation under variable conditions was carried out. Methylcobalamin had pronounced susceptibility to hydrolysis under acidic, alkaline, and photolytic conditions; further study of photolytic degradation kinetics and pH rate profiling over pH range 2–11 was carried out. Photodegradation of methylcobalamin followed zero‐order kinetics with half‐life 0.99 h equivalent to 1971.53 lux. Methylcobalamin followed pseudo‐first‐order kinetics upon exposure to acidic and alkaline hydrolysis with highest stability at pH 5 and least stability at pH 2. Optimization of chromatographic conditions was performed using two level full factorial design, and chromatographic analysis was executed using Inertsil column (250 × 4.6 mm, 5 μm) maintained at 25 ◦ C. Elution was carried out using 25 mM potassium dihydrogen phosphate (pH adjusted with phosphoric acid to 3.8): methanol:acetonitrile (55:35:10, v/v) as mobile phase. The flow rate was 1.0 ml/min. Detection was carried out at 220 nm using diode array detector. The method was validated as per ICH guidelines; the linearity was over concentration range 2–160 μg/ml with coefficient of determination 0.9995. The method was effectively applied for determination of methylcobalamin in Cobalvex ampoule, Cobal tablet, Cobal‐F tablet, and Methyltechon oral dissolvable film without interfering from excipients within run time 6 min.